2007
DOI: 10.1111/j.1750-3841.2007.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Enterobacter sakazakii in Infant Milk Formula by Gamma Irradiation: Determination of D10‐Value

Abstract: Enterobacter sakazakii is an emerging foodborne pathogen that has caused several cases of meningitis and necrotizing enterocolitis in infants and has been associated with infant formulas. Five strains of E. sakazakii were inoculated individually into brain heart infusion broth and rehydrated or dehydrated infant milk formula and exposed to ionizing radiation. E. sakazakii strains in brain heart infusion broth and rehydrated infant milk formula (RIMF) were exposed to irradiation dose of up to 1 kGy while strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 38 publications
(61 reference statements)
4
30
1
Order By: Relevance
“…These results indicate that D 10 -value of the microorganisms depend on sample thickness, initial microbial load, physicochemical properties of the sample, and irradiation and storage conditions (Lee et al, 1998(Lee et al, , 2000. In particular, the D 10 -value for E. sakazakii in our study is higher than those of other studies (Lee et al, 2007;Osaili et al, 2007). Lee et al (2007) have reported that the D 10 -value for E. sakazakii is 0.76 kGy for dehydrated infant formula using gamma irradiation.…”
Section: -Valuescontrasting
confidence: 79%
See 2 more Smart Citations
“…These results indicate that D 10 -value of the microorganisms depend on sample thickness, initial microbial load, physicochemical properties of the sample, and irradiation and storage conditions (Lee et al, 1998(Lee et al, , 2000. In particular, the D 10 -value for E. sakazakii in our study is higher than those of other studies (Lee et al, 2007;Osaili et al, 2007). Lee et al (2007) have reported that the D 10 -value for E. sakazakii is 0.76 kGy for dehydrated infant formula using gamma irradiation.…”
Section: -Valuescontrasting
confidence: 79%
“…Lee et al (2007) have reported that the D 10 -value for E. sakazakii is 0.76 kGy for dehydrated infant formula using gamma irradiation. Osaili et al (2007) also have reported that the D 10 -value is 1.71 kGy for dehydrated infant milk formula. However, it should be noted that the sample in our study was different, because powdered weaning food made from a particular formula containing rice and rice flour was used as a sample.…”
Section: -Valuesmentioning
confidence: 93%
See 1 more Smart Citation
“…A D value represents the dose required to cause one log cycle change in a measured parameter. [18][19][20] Here, we used D value to describe the irradiation dose required to change molecular weight by one log cycle and D values were calculated for composted samples after 0, 1, 2 and 6 weeks.…”
Section: Irradiation D Valuesmentioning
confidence: 99%
“…Recently, some authors have proposed several decontamination methods in an effort to reduce levels of C. sakazakii in powdered infant formula, including gamma radiation (16,17), electron beam irradiation (18), supercritical carbon dioxide and heat treatment (19), and gaseous ozone treatment (20). However, all of these methods have limitations for industrial application because of high capital costs for installation and treatment.…”
mentioning
confidence: 99%